Evaluating the cross-sectional area of the internal jugular vein in Turkish adults using ultrasonography - Özdemir Kalkan, Doğa; Kavak, Nezih (The European Research Journal, 2024)
Objective: To assess the cross-sectional area (CSA) of the right and left internal jugular veins (IJVs) in the adult Turkish population. Methods: The CSA of the IJVs was quantified at three anatomical landmarks: below the angle of the mandible, at the level of the cricothyroid membrane, and in the supraclavicular region. Measurements were taken under three conditions: at rest, during a deep breath hold, and throughout the Valsalva maneuver. Results: The study encompassed 321 volunteers with a mean age of 30.40±7.75 years. At the anatomical landmarks of the angle of the mandible, cricothyroid, and supraclavicular regions, the CSA of the IJV in men was consistently larger than in women during rest, deep breath hold, and the Valsalva maneuver. During both the deep breath hold and the Valsalva maneuver at these landmarks, the right CSA of the IJV in both genders was greater than the left CSA. In both males and females, the CSA of the IJV at the supraclavicular location was superior to that at both the angle of the mandible and the cricothyroid regions. The CSA at the cricothyroid regions surpassed that at the angle of the mandible. Conclusions: The CSA of the IJV was found to be the largest in the right supraclavicular region during the Valsalva maneuver in both genders. By accurately measuring the CSA of the IJV at the angle of the mandible, cricothyroid, and supraclavicular anatomical landmarks during a deep breath hold and the Valsalva maneuver, potential interventional and surgical risks can be mitigated.